Meminimalkan Biaya operasional dan Memaksimalkan Kepuasan Pelanggan dalam Perusahaan Transportasi Laut di PT XYZ Jakarta - Agung kwartama; Samiyono Samiyono (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
In the maritime transportation industry, companies face challenges in minimizing operational costs while maximizing customer satisfaction. PT XYZ, as one of the leading maritime transportation companies, needs to adopt effective strategies to achieve these objectives. This study aims to identify cost-efficiency methods that can be implemented and analyze the impact of costs on customer satisfaction. By using relevant data and case studies, this research is expected to provide in-depth insights for PT XYZ's management in making strategic decisions.